Leptospirosis in the department of Córdoba, Colombia (1978)
Leptospirosis is a disease which mani fest itself in a number ways in almost all domestic animals and causes considerable to livestock producers. In cattle, visible losses are incurred mainly through abortion, stillbirth and perinatal mortality. wuile acute disease and a mastitis-like syndrome are less cojnmon. Furthermore, field evidence sugs:ests that leptospirosis can he made responsible for increased ca1ving-toconception intervals, thus lari log to invisible losses which possibly exceed those directly discernible by the producer. 'Fh.re is a large volume of literature on leptospirosis, but. few attempts have been made systematically to assess the imoortance and interactions of the different determinants of the disease. Environmental conditions and management practices strongly influence the dynamics of the infection and it appears that each farming ecosystem may create its own epidemiology. Many cualitative and especially quantitative aspects of the epidemiology of leptospirosis are still poorly understood. Simiirly, the economic impact of leptospirosis has not been assessed comprehensively yet in ariy single production system. Serological investigations have shown leptcspiral. infections to be widely spread in cattle populations mantained in. tropical environments. The biological and economic significance of these infections, however, has yet to be ascertained and estimates of economic imoacts made so far should he regarded with some caution.